Cell wall response of field grown Populus to Septoria infection - Bryant, Nathan; Muchero, Wellington; Weber, Rachel A.; Barros, Jaime; Chen, Jin-Gui; Tschaplinski, Timothy J.; Pu, Yunqiao; Ragauskas, Arthur J. (Frontiers in Plant Science, 2023)
Due to its ability to spread quickly and result in tree mortality, Sphaerulina musiva (Septoria) is one of the most severe diseases impacting Populus. Previous studies have identified that Septoria infection induces differential expression of phenylpropanoid biosynthesis genes. However, more extensive characterization of changes to lignin in response to Septoria infection is lacking. To study the changes of lignin due to Septoria infection, four field grown, naturally variant Populus trichocarpa exhibiting visible signs of Septoria infection were sampled at health, infected, and reaction zone regions for cell wall characterization. Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and acid hydrolysis were applied to identify changes to the cell wall, and especially lignin. FTIR and subsequent principal component analysis revealed that infected and reaction zone regions were similar and could be distinguished from the non-infected (healthy) region. NMR results indicated the general trend that infected region had a higher syringyl:guaiacyl ratio and lower p-hydroxybenzoate content than the healthy regions from the same genotype. Finally, Klason lignin content in the infected and/or reaction zone regions was shown to be higher than healthy region, which is consistent with previous observations of periderm development and metabolite profiling. These results provide insights on the response of Populus wood characteristics to Septoria infection, especially between healthy and infected region within the same genotype.